Wildlife conservation video collaboration & a USR visit to Zoo Taiping / Noor Azli Affendy Lee, Muhammad Aiman Abdul Halim & Nur Ilianis Adnan - Affendy Lee, Noor Azli (Academy of Language Studies, 2022)
The English Language Club of UiTMCPP conducted a two-pronged programme to raise awareness on the welfare of animals. The Wildlife Conservation Week and Taiping Zoo Volunteer and Visit 2022, with the theme “Conserve, Preserve, Reserve (CPR) Wildlife” aims to educate students in wildlife preservation and conservation. In addition, this programme hoped to raise awareness among youths and the general public about the importance of animal rescue and conservation, especially those classified as critically endangered. This programme was a part of an effort to educate the community about the plight of endangered species and actions that could be taken to help improve the situation.